E-commerce adoption research: a review of literature - Khoo, Vivian; Ahmi, Aidi; Saad, Ram Al Jaffri (Academic Research Publishing Group, 2018)
The purpose of this paper is to provide a comprehensive literature review of the e-commerce adoption studies. This paper investigated the papers that have been published and indexed in the Scopus database for the period from 2012- 2017. This study found that e-commerce adoption studies can be classified into six themes: factors affecting e-commerce adoption, barrier of e commerce adoption, implication of e-commerce adoption, e-commerce adoption process, improvement of e-commerce adoption and e-commerce web attraction. It is found that existing literature has given considerable attention to the drivers that facilitate e-commerce adoption while other themes have received far less attention from researchers. The significant factors that influence e-commerce adoption includes management’s support, the role of government, perceived benefits, external pressures, organizational readiness, IT-related skills, capabilities and infrastructure, among others. Such limited scope of study efforts could only provide a stagnant view towards partial understanding of the dynamic diffusion process of e-commerce. Future research shall be extended to explore e-commerce adoption from the process perspective and investigate the post-adoption stages of e-commerce to observe how e-commerce adoption evolves over time.